The Effect of Treatment on Serum C3, C4, IL-10, IL1-β, IL-6, TNF-α in Patients with Systemic Lupus Erythematosus : Serum C3 and C4, IL-10, IL1-β, IL-6, TNF-α in SLE - Reyimu, Nadira; Jing, Yueyue (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the effects of structured lifestyle optimization, including nutritional intake and exercise training, on serum levels of Complement C3, C4, IL-10, IL1-β, IL-6, and TNF-α in patients with systemic lupus erythematosus (SLE) and Libman-Sacks endocarditis (LSE). Methods: A total of 122 SLE patients with LSE, treated at our hospital from May 2022 to May 2024, were randomized into a control group (CG, n=61) receiving conventional medical interventions and an intervention group (IG, n=61) receiving additional personalized exercise and nutritional interventions for 24 weeks. Serum levels of Complement C3, C4, IL-10, IL1-β, IL-6, and TNF-α were measured at baseline, 3 months, and 6 months. Secondary endpoints included nutritional status (albumin, hemoglobin) and patient compliance. Results: Of 113 patients completing the study, the intervention group (IG) showed significant improvement in serum Complement C3 (0.84 ± 0.18 g/L vs. 0.75 ± 0.16 g/L in control group [CG], P=0.006) and albumin levels (37.12 ± 5.37 g/L vs. 35.00 ± 4.89 g/L, P=0.03) at 6 months. Complement C4 levels increased in the IG (0.20 ± 0.09 g/L vs. 0.17 ± 0.12 g/L, P=0.136, not significant). IL-1β (3.9 ± 3.77 pg/mL vs. 4.6 ± 4.1 pg/mL, P=0.468) and TNF-α (12.6 ± 4.1 pg/mL vs. 14.1 ± 5.2 pg/mL, P=0.092) showed non-significant reductions in the IG compared to the CG. No significant changes were observed in IL-10 or IL-6 levels. Compliance was significantly higher in the IG (92.86% vs. 78.95%, P=0.038). Conclusion: Structured lifestyle optimization significantly improved serum Complement C3 and albumin levels and showed non-significant trends toward reductions in IL-1β and TNF-α in SLE patients with LSE, suggesting a potential adjunctive role in managing immune and nutritional status.